MCDM-Based Wildfire Risk Assessment: A Case Study on the State of Arizona - Pishahang, Mohammad; Jovčić, Stefan; Sarfaraz Hashemkhani, Zolfani; Simić, Vladimir; Görçün, Ömer Faruk (My University, 2023)
The increasing frequency of wildfires has posed significant challenges to communities worldwide. The effectiveness of all aspects of disaster management depends on a credible estimation of the prevailing risk. Risk, the product of a hazard’s likelihood and its potential consequences, encompasses the probability of hazard occurrence, the exposure of assets to these hazards, existing vulnerabilities that amplify the consequences, and the capacity to manage, mitigate, and recover from their consequences. This paper employs the multiple criteria decision-making (MCDM) framework, which produces reliable results and allows for the customization of the relative importance of factors based on expert opinions. Utilizing the AROMAN algorithm, the study ranks counties in the state of Arizona according to their wildfire risk, drawing upon 25 factors categorized into expected annual loss, community resilience, and social vulnerability. A sensitivity analysis demonstrates the stability of the results when model parameters are altered, reinforcing the robustness of this approach in disaster risk assessment. While the paper primarily focuses on enhancing the safety of human communities in the context of wildfires, it highlights the versatility of the methodology, which can be applied to other natural hazards and accommodate more subjective risk and safety assessments
Hodnocení rizika lesních požárů na základě MCDM: případová studie o státě Arizona
Keywords: MCDM-Based; Wildfire Risk Assessment; Case Study; the State Arizona; Hodnocení rizika lesních požárů; MCDM; případová studie; stát Arizona